How many loci does it take to DNA barcode a crocus? - Ole Seberg (Public Library of Science (PLoS), 2009)
Background DNA barcoding promises to revolutionize the way taxonomists work, facilitating species identification by using small, standardized portions of the genome as substitutes for morphology. The concept has gained considerable momentum in many animal groups, but the higher plant world has been largely recalcitrant to the effort. In plants, efforts are concentrated on various regions of the plastid genome, but no agreement exists as to what kinds of regions are ideal, though most researchers agree that more than one region is necessary. One reason for this discrepancy is differences in the tests that are used to evaluate the performance of the proposed regions. Most tests have been made in a floristic setting, where the genetic distance and therefore the level of variation of the regions between taxa is large, or in a limited set of congeneric species. Methodology and principal findings Here we present the first in-depth coverage of a large taxonomic group, all 86 known species (except two doubtful ones) of crocus. Even six average-sized barcode regions do not identify all crocus species. This is currently an unrealistic burden in a barcode context. Whereas most proposed regions work well in a floristic context, the majority will--as is the case in crocus--undoubtedly be less efficient in a taxonomic setting. However, a reasonable but less than perfect level of identification may be reached--even in a taxonomic context. Conclusions/significance The time is ripe for selecting barcode regions in plants, and for prudent examination of their utility. Thus, there is no reason for the plant community to hold back the barcoding effort by continued search for the Holy Grail. We must acknowledge that an emerging system will be far from perfect, fraught with problems and work best in a floristic setting.